2016
DOI: 10.1152/jn.00606.2015
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the physiological and behavioral roles of proctolin inDrosophila melanogaster

Abstract: The neuropeptide proctolin (RYLPT) plays important roles as both a neurohormone and a cotransmitter in arthropod neuromuscular systems. We used third-instar Drosophila larvae as a model system to differentiate synaptic effects of this peptide from its direct effects on muscle contractility and to determine whether proctolin can work in a cell-selective manner on muscle fibers. Proctolin did not appear to alter the amplitude of excitatory junctional potentials but did induce sustained muscle contractions in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 76 publications
1
33
0
Order By: Relevance
“…Similarly, other neuropeptides previously described as gut-brain neuropeptides, such as CRF-DH44 (Cannell et al, 2016), diuretic hormone 31/calcitonin-like peptide, and diuretic hormone 45, also appear to be expressed in both the brain and gut of S. exigua. Additional gut-brain peptides identified in our transcriptomic approach are proctolin (Ormerod et al, 2016), myosuppressin (Vilaplana et al, 2008), neuropeptide F1, short neuropeptide F (Nässel and Wegener, 2011), tachykinin (Song et al, 2014) and orcokinin (OK; Sterkel et al, 2012).…”
Section: Gut-brain Neuropeptidesmentioning
confidence: 99%
“…Similarly, other neuropeptides previously described as gut-brain neuropeptides, such as CRF-DH44 (Cannell et al, 2016), diuretic hormone 31/calcitonin-like peptide, and diuretic hormone 45, also appear to be expressed in both the brain and gut of S. exigua. Additional gut-brain peptides identified in our transcriptomic approach are proctolin (Ormerod et al, 2016), myosuppressin (Vilaplana et al, 2008), neuropeptide F1, short neuropeptide F (Nässel and Wegener, 2011), tachykinin (Song et al, 2014) and orcokinin (OK; Sterkel et al, 2012).…”
Section: Gut-brain Neuropeptidesmentioning
confidence: 99%
“…Physiological effects of proctolin on body wall muscles of 3rd instar larvae (Ormerod et al, 2016) suggest proctolin receptor expression. Proctolin increases the amplitude of nerve-evoked contractions at low concentrations (EC 50 2 nM) and induces contractions at much higher concentrations (EC 50 900 nM).…”
Section: Proctolinmentioning
confidence: 99%
“…RNAi expression in neurons did not alter proctolin's effect, suggesting a postsynaptic action but no presynaptic action, and proctolin did not alter muscle EJPs. Proctolin-induced contractions involve extracellular Ca 2þ and intracellular Ca 2þ stores and are antagonized by the L-type channel blocker, nifedipine and an inhibitor of store-operated calcium channels (Ormerod et al, 2016). Muscle ablation indicated that proctolin induces contractions more strongly in muscles 4, 12 and 13 than in 6 and 7, and proctolin also enhances nerve-evoked contractions more strongly in 4, 12 and 13 than in 6 and 7 (Ormerod et al, 2016).…”
Section: Proctolinmentioning
confidence: 99%
See 1 more Smart Citation
“…To isolate contraction force mediated predominantly by the dorsal muscle 342 group (M1, M2, M3, M9, M10), 3 rd instar larvae were dissected along the ventral midline. Severed 343 abdominal nerves were placed in a suction electrode and the nerve bundle was stimulated at 344 increasing frequencies in HL3.1 saline containing 1.5 mM extracellular Ca 2+ as previously 345 described(Ormerod et al, 2016). Control MN1-Ib and MNIs GAL4 larval preparations showed 346 increasing contraction force when a 0.1 msec simulation was ramped from 1 Hz to 150 Hz for 600 347 ms (Figure 4E).…”
mentioning
confidence: 95%